2015
DOI: 10.1111/ggi.12602
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory hypothesis as a link between Alzheimer's disease and diabetes mellitus

Abstract: Our findings support the presence of a low-grade systemic inflammation link between AD and DM. Geriatr Gerontol Int 2016; 16: 1161-1166.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Traditionally, AD and DM have been considered two independent diseases. However, recent studies have shown that they share several pathophysiological mechanisms, including specific inflammatory signaling pathways (Bozluolcay et al, 2015), oxidative stress, and cell apoptosis. For example, in FIGURE 4 | Sirt1 expression in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, AD and DM have been considered two independent diseases. However, recent studies have shown that they share several pathophysiological mechanisms, including specific inflammatory signaling pathways (Bozluolcay et al, 2015), oxidative stress, and cell apoptosis. For example, in FIGURE 4 | Sirt1 expression in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Both AD and type 2 diabetes involve chronic inflammation and share similar pathological features including insulin resistance, hyperglycemia, and increased advanced glycation end-products. 58 Patients with type 2 diabetes have an increased risk of developing AD. 59 This is likely because impaired insulin signaling attenuates the production and function of insulindegrading enzyme in the brain, which might lead to inefficient Aβ clearance.…”
Section: Neuroinflammation In Ad Progressionmentioning
confidence: 99%
“…Both AD and type 2 diabetes involve chronic inflammation and share similar pathological features including insulin resistance, hyperglycemia, and increased advanced glycation end-products . Patients with type 2 diabetes have an increased risk of developing AD .…”
Section: Clinical Trials Of Drugs With Anti-inflammatory Effectsmentioning
confidence: 99%
“…101 Both medial temporal lobe atrophy 98,99 and hippocampal volumes 102 with cerebral SVD are associated with conversion to AD or the other subtypes of dementia in MCI patients. Atrial fibrillation and diabetes could also be a risk factor for AD and VaD, 103,104 in addition to stroke. 105 These results support the notion that individuals with vascular pathologies have increased odds of dementia compared with individuals with a single pathology.…”
Section: Cognitive Impairmentmentioning
confidence: 99%